Influence of laser power on molten pool flow field of laser-MIG hybrid welded Invar alloy. (January 2021) - Yan, Tingyan; Zhan, Xiaohong; Gao, Qiyu; Wang, Feiyun; Ling, Wanli
Highlights: It was clarified that the keyhole growth is mainly divided into three characteristic stages. Increasing the laser power will accelerate the growth rate of keyhole depth. When the laser energy is increased, the fluid flow around the keyhole becomes more intense and rapid gradually. Abstract: The dynamic behavior of molten pool and keyhole is highly related to the parameters of welding process. The current study adopted a three-dimensional numerical model to investigate the effect of laser power on the flow field, which under the condition of considering the keyhole and molten pool dynamic behaviors in Laser-MIG hybrid welding. On this basis, the influence mechanism of laser power on the keyhole morphology, velocity field of molten pool and fluid flow behavior was analyzed comprehensively. The model incorporates consideration of the influence of surface tension, recoil pressure, the Marangoni force, electromagnetic force, buoyancy, etc. The transfers of heat, mass and momentum caused by liquid flow and droplet transfer were considered. The simulation results indicated that the depth of keyhole was mostly impacted by the laser power. The increase of laser power was beneficial to obtain weld seam with larger depth-to-width ratio. Moreover, the fluid flow around the keyhole became more intense and rapid gradually when the laser energy was increased.